Hubungan pemenuhan kebutuhan spritual dasar dengan tingkat status mental pada orang dalam gangguan jiwa diyayasan berkas bersinar abadi lamongan - Supriadi, Bambang; Sholikhah, Siti; Saifudin, Moh. (Jurnal Keperawatan Muhammadiyah, 2025)
The fulfillment of spiritual needs is essential for individuals with mental disorders, as it plays a significant role in supporting mental stability and improvement. Spirituality provides meaning in life, hope, and inner peace, all of which have positive effects on patients’ psychological well-being. This study aims to examine the relationship between the fulfillment of basic spiritual needs and mental status levels in individuals with mental disorders at the Berkas Bersinar Abadi Foundation in Lamongan. This research employed a cross-sectional design with a population of 80 individuals with mental disorders, from which 66 participants were selected using a random sampling technique. The research instrument was a structured questionnaire, and the data were analyzed using Spearman’s rho test with a significance level of p < 0.05. The results showed that most respondents (88.3%) had low fulfillment of basic spiritual needs, while a majority (59.1%) exhibited good mental status. The statistical analysis yielded a significance value of p = 0.000 (p < 0.05) with a correlation coefficient (rₛ) of 0.566, indicating a moderately strong positive relationship between the fulfillment of basic spiritual needs and mental status. The higher the level of spiritual fulfillment, the better the mental status observed. These findings highlight the importance of integrating spiritual aspects into mental health care. Therefore, it is recommended that nurses develop spiritually-based programs, such as regular group worship and religiously oriented support groups, as part of a holistic rehabilitation intervention.